The Flexible and Transparent Film Heaters Based on Regenerated Cellulose and Carbon Nanotubes - Cui, Jiedong; Lu, Pengbo; Li, Yinghui; Xu, Ke; Li, Yang; Shen, Haoyu; Liu, Chaocheng; Zhang, Tianyi; Liu, Detao (Frontiers in Energy Research, 2022)
The flexible and transparent film heaters (FTFHs) with the advantages of mechanical flexibility, portability, and excellent electrothermal performance, are key to the next generation portable, wearable heaters and thermal protection systems. However, the present flexible and transparent substrates of FTFHs are fabricated by typical plastic PET films, which suffer from poor interfacial adhesion with the thermally conductive materials. In this work, the transparent regenerated cellulose fibers made of completely dissolved in NMMO solution followed by regeneration process is presented to disperse and support carbon nanotubes (CNTs) by a vacuum-dewatering process. In the presence of cellulose fibers, these CNTs have strong hydrogen bonding properties in the dehydration-deposition process and thus respond to tight intertwining structures in fibrous composites. The resulting regenerated cellulose fibers exhibit high optical transparency of 88% (@550 nm) and good mechanical properties (30 MPa). Interestingly, the FTFHs show a rapid heating response, high generation temperature, and resistance stability for up to 2 h. The FTFHs made with earth-abundant, cost-effective, and recyclable materials, have excellent potential in the areas of green flexible and transparent film heaters.